Options to Increase Access to Telecommunications Services in Rural and Low-Income Areas - Muente-Kunigami, Arturo; Navas-Sabater, Juan (World Bank, 2012)
Recent evidence suggests that increasing overall service coverage and promoting access to telecommunications services have a high economic benefit. Overall, it is estimated that a ten percent increase in mobile telephony penetration could increase economic growth by 0.81 percent in developing countries, whereas a ten percent increase in broadband penetration could increase economic growth by 1.4 percent. In rural and low-income areas in particular, not only do basic telephony services and broadband access allow population to connect with relatives and friends, but they have also introduced a dramatic increase in productivity and in many cases have become the only way for small and medium enterprises in rural areas to access national and, in some cases, global markets. Moreover, the impact of access to telecommunications in rural areas on health, education, disaster management, and local governments has allowed better and more rapid responses, improved coordination, and more effective public management. It is therefore worthwhile to take a second look at all possible policy options, both conventional mechanisms (some of which underutilized) as well as new approaches, to determine whether some of them may be relevant for the emerging agenda of universal broadband access. This paper will first address the necessary conditions required to adopt a more ambitious universal access policy in developing countries. After that, a brief account of the main relevant trends in the industry will be made, followed by a description of twelve different mechanisms for project implementation and six different mechanisms for funding of universal access strategies. Then, an evaluation of the mechanisms will be carried out to identify the most suitable ones. Finally, some recommendations to policy makers on implementation of the preferred mechanisms are also drawn from the analysis.